Preserving Cultural Heritage Through a Traditional Ritual: A Case of Kabuyutan Ciburuy - Nyai Kartika; Reiza D. Dienaputra; Susi Machdalena; Nani Sriwardani; Yully Ambarsih Ekawardhani; Dadang Sudrajat (LP2M ISBI Bandung, 2024)
The Seba ceremony in Kabuyutan Ciburuy is a tradition of preserving cultural heritage that has been carried out for generations. Currently, Kabuyutan Ciburuy is no longer actively used as an educational institution, nor are the contents of its ancient manuscripts used as a reference for the development of science. For this reason, this research tries to dissect why this happens. This research uses a qualitative research method which is believed to be a scalpel in research, thereby helping to explain the research object factually. The research step is to carry out participant observation, the researcher actively participates in the activities being researched. Also hold interviews with local cultural figures either formally or informally. The result of this research is a descriptive explanation of the Seba Ceremony as an effort to preserve cultural heritage. Because heirlooms refer to educational activities, such as the discovery of many manuscripts, one of which contains advice on old Sundanese character and ethics. This has become a high level of cultural wealth by continuing to carry out the Seba ceremony as a form of preservation so that it remains alive and relevant for future generations. Keywords: Seba Ceremony, Ciburuy District, Preservation, Cultural Heritage